Absceso de espacios profundos del cuello: a propósito de un caso en un niño - Bravo C., Gustavo; Martelo P., Grettel; Celedón L., Carlos; Seymour M., Camila (Revista Hospital Clínico Universidad de Chile, 2011)
Infections of the deep neck spaces are low-frequency entities. They can be classified according to the anatomical space committed to peritonsillar, parapharyngeal, retropharyngeal, etc. They are clinically similar to other upper respiratory infection with symptoms like: fever, sore throat, dysphagia, dysphonia, cervical lymphadenitis. The diagnosis is made by clinical history, physical examination findings and imaging studies. The treatment consists in securing the airway, intravenous antibiotics and surgical drainage. We report the case of a ten months years old child who consulted at the Hospital Clínico Universidad de Chile by an upper respiratory infection associated with right cervical enlargement. The neck CT scan showed extensive soft tissue inflammatory changes of right lateral cervical region, supra and infrahyoid. The diagnosis of right deep neck space abscess was made. We began treatment with Cefotaxime /Clindamycin, and surgical drainage, showing favorable results.